Establishment Age and Wages: Evidence from German Linked Employer-Employee Data - Arnd Kölling; Claus Schnabel; Joachim Wagner (Institute for the Study of Labor (IZA), 2002)
Research in wage differentials has a long tradition. Prominent reasons why people make more or less money in the labor market include personal characteristics of the employee (e.g., human capital or gender), job characteristics (working conditions demanding compensating wage differentials), and characteristics of the employer (e.g., industry or firm size). An emerging empirical literature suggests that one hitherto overlooked firm characteristic matters, too: Employers which are in business for a longer period of time tend to pay higher wages. Using a unique rich set of linked employer-employee data we present first empirical evidence on this firm age - wage nexus for Germany. We find that older firms pay on average higher wages for workers with the same broadly defined degree of formal qualification. This firm age differential vanishes after controlling for further worker characteristics and other firm characteristics besides age; if anything, younger firms pay more ceteris paribus. These results are in line with findings from a recent study by Brown and Medoff using U.S. data.
Keywords: J3; 330; establishment age; wage; linked employer-employee data; Germany; Lohn; Unternehmensentwicklung; Dauer; Lohnstruktur; Schätzung; Deutschland